VD_FINDINFO HC / 2014 / 582 vom 12. Juni 2014 - VD Tribunal cantonal (2014)
AUTORITÉ PARENTALE, DROIT DE GARDE, OBLIGATION D'ENTRETIEN, PROTECTION DE L'UNION CONJUGALE | 176 al. 1 CC, 176 al. 3 CC, 297 al. 2 CC